First Nations Community of Inquiry & Praxis (FNCIP) - Lefebvre, Joette; Hedican, Tara (Scholarship@Western, 2021)
The First Nations Community of Inquiry & Praxis (FNCIP) is a group of Indigenous intellectuals working together to support each other and the First Nations With Schools Collective (FNWSC). FNCIP was founded by the FNWSC and an Indigenous faculty member partner employed at Western University’s Faculty of Education. FNCIP aims to conduct inquiries and praxis that originate out of interest and relevance to its members, and to the FNWSC’s mandate in supporting lifelong learning that is Indigenous-centered and grounded in Indigenous philosophies of knowing, being and doing. Through regularly scheduled inquiry-based discussions, FNCIP members principally participate in the co-production of knowledge and a communityminded approach that serves as an educational advisory group on topics of significance to the FNWSC. Additionally, FNCIP members seek to mobilize transformative educational praxis among FNCIP members and in their individual community contexts, generally. The FNWSC recognizes the on-going participation of FNCIP members and FNWSC delegates as a vital contribution toward sustaining and building educational excellence among FNWSC members First Nations citizenry. FNCIP webinars presentations 12-14 conducted PAGE 28 between March 5, 2021, and August 4, 2021, will be discussed for this presentation. https://ir.lib.uwo.ca/headandheartprogram_2021/1011/thumbnail.jpg